Teaching strategies that teachers use to improve reading and writing in English as first additional language : case study - Lumadi, Thabelo Zacharia (University of Limpopo, 2016)
This study reflects on the teaching strategies that that teachers use to improve reading and writing in English FAL in the Acornhoek area of Mpumalanga Province. Since the study wanted to have an in-depth understanding of the strategies that teachers use to improve reading and writing, a qualitative methodology was used. It is within this methodology that a case study was adopted whereby three methods of data collection were used, namely: interviewing, observation and documents. Two schools were selected as sites for the study by means of purposive sampling. The participants interviewed included teachers and learners. The documents consulted included learners class work books, assignments and tests scripts. The researcher also observed lessons that were presented by the teachers. This study found that learners have difficulties in reading and writing, for example, they cannot punctuate, pronounce and spell words correctly. Furthermore, the study also found that teachers were not trained to deal with reading and writing difficulties. This is manifested by the strategies that they use to improve reading and writing, for example, lack of use of repetition which they claimed to use during interviews. KEY WORDS Reading, Writing, Difficulties, Strategies, Constraints, Improve
Thesis (M. Ed.) -- University of Limpopo, 2016
Keywords: Reading difficulties; Writing difficulties; Teaching strategies; Reading; Effective teaching